Are saponins and sapogenins precursors of prednisolone? Preliminary results (International Journal of Health, Animal Science and Food Safety, 2015)
The transformation of cortisol into prednisolone in cattle faeces was demonstrated and provided by literature, given the structural similarity of prednisolone with cortisol. In this study, we evaluated a possible neo-formation of prednisolone, as results of a faecal or environmental contamination. A saponine, α-solanine, and a sapogenin, diosgenin, were selected as possible precursors. A simple method without extraction was applied. The analyses were performed by HPLC–MSn to evaluate the possible transformations. The results showed that prednisolone was detected in the faecal suspension spiked with diosgenin at t= 8h, while cortisol was also detected at t = 24h in the sample of faeces spiked with α-solanine. In the feed and in the control samples, no transformations were observed.
Keywords: saponins; sapogenins; prednisolone; Saponins; neoformation; faeces; feed